Sacralizing the nation through remembrance of medieval religious figures in Serbia, Bulgaria and Macedonia. - Rohdewald, Stefan, 1972- (East Central and Eastern Europe in the Middle Ages, 450-1450,, 2022)
Religious figures of remembrance served to consolidate first dynastic rule and later nation-state legitimacy and community. This book explains the interweaving of (Eastern) Roman, medieval Serbian and Bulgarian contexts as well as Ottoman and Western European national discourses or reinvented traditions. We can distinguish a secularization and nationalization of the religious contexts in the 19th century within historicism, followed by a nationalization of God and a sacralization of the nation until the end of WWII. Contrary to the national views, the origins of the modern content of these discourses lie only to a very limited extent in the Middle Ages or in the Early Modern period, as this study shows.